Mutations associated with drug resistance and prevalence of vaccine escape mutations in patients with chronic hepatitis B infection. Issue 10 (21st July 2017) - dos Santos, Maria Isabel Magalhães A.; Pacheco, Sidelcina Rugieri; Stocker, Andreas; Schinoni, Maria Isabel; Paraná, Raymundo; Reis, Mitermayer G.; Silva, Luciano K.
Abstract : The Brazilian public health system (SUS) has provided antiviral drugs for chronic hepatitis B treatment for over 10 years, but a system for monitoring for drug‐related resistance mutations is not available. Determine the presence of HBV mutations associated with resistance to nucleos(t)ide analogs among 81 patients with chronic HBV infection in Salvador—BA—Brazil. HBV‐DNA was PCR amplified with primers deduced from the rt domain at the HBV P gene, the sequence extended 1032 bp (from amino acid 1 to 344—rt domain). Those sequences were submitted to the HBV drug resistance database to retrieve each mutation according to the genotype. HBV genotype A1 (85.2%) was the most prevalent, followed by genotype A2 (4.9%), F (6.2%), and C1, D2, and D4 (1.2% each). Six patients (7%) exhibited resistance mutations to LAM, ETV, and TDF: two with patterns L180M + M204V and four with other different patterns: L80I + L180M + M204I; L80V + L180M + M204V; M204I; A194T. All of these mutations were present in patients with genotype A (four A1 and two A2). In addition, four mutations in gene S (three cases with the sI195M mutation and one with the W196L mutation), were detected, corresponding to a rate of 6% of vaccine escape mutations. Althougth the small sample size, an association was found between the occurrence of HBV resistance mutations and HBeAg positivity, co‐infection with HIV and a history of treatment for HBV and/or HIV.